Analisis faktor-faktor penyebab keterlambatan mahasiswa dalam menyelesaikan tugas akhir (skripsi) pada mahasiswa prodi PPkn - Sari, Nyi Nawang; Salam, M.; Usmanto, Heri (Citizenship Education, Faculty of Education, Jambi University, 2022)
Abstract: Student delays in completing thesis are problems that are always faced by students in the final semester. In the process of education as a student to obtain a bachelor's degree, students will be faced with a thesis final project. Thesiis is a terim usied to define a scientific paper in the form of an explanation of the results of undergraduate researich that diiscusses a proiblem or phenomienon in a partiicular fiield of science by usiing applicable rules. Students who are able to write and compile theses are considered to be able to combine their knowledge and skills in understanding, analyzing, describing, and explaiining problems related to the scientiific field they take. However, ini realiity miany studeints have diifficulty in completing their thesis, so it is not uncommon for studenits to complete theiir thesis beyond the allotted time or more than four years. This study aiims to identifiy and describe the factors that cause studeints to be late in completing their final project (thesis). This research was conducited using qualiitative reseairch methods wiith source analysis techniques and Miles and Hubermen model analysis. The results showed that the factors that caused students to be late in completing their final assignments (thesis) in the Pancasila and Civic Education study program at Jambi University were influenced by two factors, namely internal factors and external factors. The first is the lack of motivation to graduate on time and assumes that writing the thesis is difficult, the second is the individual's self-intelligence (IQ), emotional intelligence and spiritual intelligence. The third is external factors, namely the lack of availability of learning resources in libraries such as books, journals, and articles. scientific as a source of reference in the thesis. The fourth factor is the environmental factor of peers or playmates. Another factor that is also a support is the family's economic factor that requires students to work for extra money and also the hard upbringing factor of parents which makes students depressed.